Acute Promyelocytic Leukemia Presenting as Ischemic Stroke in Young - Kapoor, Rajan (Springer-Verlag, 2012)
Coagulopathy in acute promyelocytic leukemia (APL) is a very complex disorder and is believed to result from interplay of various factors. Usually patients present with bleeding tendencies which can be life threatening. However, a few present with thromboses. Here, we report a young male with APL who presented with ischemic stroke in young.